1998
DOI: 10.1128/mcb.18.9.5404
|View full text |Cite
|
Sign up to set email alerts
|

The Exon Splicing Silencer in Human Immunodeficiency Virus Type 1 Tat Exon 3 Is Bipartite and Acts Early in Spliceosome Assembly

Abstract: Inefficient splicing of human immunodeficiency virus type 1 (HIV-1) RNA is necessary to preserve unspliced and singly spliced viral RNAs for transport to the cytoplasm by the Rev-dependent pathway. Signals within the HIV-1 genome that control the rate of splicing include weak 3 splice sites, exon splicing enhancers (ESE), and exon splicing silencers (ESS). We have previously shown that an ESS present within tat exon 2 (ESS2) and a suboptimal 3 splice site together act to inhibit splicing at the 3 splice site f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 52 publications
(61 reference statements)
5
64
1
Order By: Relevance
“…This prediction was based on previous work (21) showing that this core sequence inhibits splicing of HIV tat exon 3. However, deletions E⌬9 and E⌬10 that span the TTAG sequence, rather than increasing E10 inclusion, do not alter or actually reduce E10 inclusion, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This prediction was based on previous work (21) showing that this core sequence inhibits splicing of HIV tat exon 3. However, deletions E⌬9 and E⌬10 that span the TTAG sequence, rather than increasing E10 inclusion, do not alter or actually reduce E10 inclusion, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This deletion removes a previously identified cryptic exon (20). Note that the portion of HIV tat exon 3 used in pSPL3 does not contain the splicing inhibitory sequence TTAG (21) that is also present in tau E10. A 177-bp genomic fragment containing human tau E10 with 33 and 51 bp of flanking intron sequences was amplified from P1 artificial chromosome clone 4139 by PCR using forward and reverse primers I9X2 (5Ј-CCACTCGAGCGTGTCACT-CATCCTTTTTC-3Ј) and I10B2 (5Ј-CGGGATCCTAATAATTCAAGCCA-CAG-3Ј) that contain an XhoI and BamHI site, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This regulation is exercised at several levels. At the level of cis-acting signals, splicing is controlled by the suboptimal nature of the 3Ј splice sites (Staffa and Cochrane 1994;O'Reilly et al 1995) as well as the exon splicing enhancers (ESEs) and exon splicing silencers (ESSs) throughout the RNA, which act to promote and inhibit recognition of the adjacent splice site, respectively (Amendt et al 1994;Staffa and Cochrane 1995;Si et al 1998;Caputi et al 1999;Bilodeau et al 2001). Moreover, the ESE and ESS within the terminal exon also regulate viral RNA transport.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these various sites gives rise to at least 35 different mRNAs (1). Although the relative efficiencies of the HIV-1 donor sites seem to depend mainly upon their complementarity to the U1 snRNA 5Ј-terminal sequence (3,4), efficiencies of HIV-1 acceptor sites depend upon the presence of cis-regulatory elements (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies have shown that HIV-1 acceptor sites are suboptimal as follows.…”
mentioning
confidence: 99%